Periodate Oxidation of Acacia auriculiformis Gum Polysaccharide - Singh, R.B. (Asian Journal of Chemistry, 2010)
Periodate oxidations is the most important reaction in the structure determination of polysaccharides. It was done by using sod. metaperiodate as oxidant; results showed the consumption of 6.05 moles of periodate and liberation of 1.24 moles of formic acid per equivalent of gum.